Influence Of Breastfeeding Practices on Nutritional Status of Children Among Tea Garden Workers - Netri, Das; Alak, Barua (National Journal of Community Medicine, 2016)
Background: Although breastfeeding is nearly universal in India, malnutrition still remains a major threat to survival, growth and development of Indian children. Objectives: The objectives of the study were to assess nutritional status of children by anthropometry in the Tea Garden Community in Dibrugarh district of Assam and to find its association with breastfeeding practices Methods: A community-based cross-sectional study was conducted among 390 children aged 12-24 months in six randomly selected tea gardens of Dibrugarh district from October 2011 to June 2012. Nutritional assessment was done by using weight-for-age, height-for-age and weight-for-height. Results: Prevalence of underweight, stunting and wasting was 61.5%, 65.6% and 33.8% respectively. Delayed initiation breastfeeding, prelacteal feeding, deprivation of colostrum, not exclusively breastfeeding for six months and improper complementary feeding were significant risk factors for underweight. Stunting was significantly more among children who were not exclusively breastfed and with improper complementary feeding. Prelacteal feeding and colostrum deprivation were significant risk factors for wasting. Conclusion: This study reflects a high prevalence of undernutrition among children of Tea Garden Community which is significantly associated with improper breastfeeding practices.